2017
DOI: 10.17560/atp.v59i01-02.620
|View full text |Cite
|
Sign up to set email alerts
|

Namur Open Architecture

Abstract: Die durch die klassische Namur-Pyramide beschriebene Automatisierungsstruktur ist bewährt und ermöglicht langjährige Betriebssicherheit. Allerdings fehlt den Systemen die Offenheit, neue Technologien werden erst spät verwendet und die Kosten sind hoch, was angesichts der rasanten Entwicklungen im Bereich von Internet of Things, Industrie 4.0, Mobile Devices und Big Data nutzvolle Innovationen verhindert. In diesem Beitrag wird das im Namur-Arbeitskreis 2.8 Automatisierungsnetzwerke und -dienste entwickelte Kon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 7 publications
0
7
0
2
Order By: Relevance
“…Companies have also started to completely digitize their asset and plant plans. The question whether the high amount of information needs to be integrated in the classical pyramid automation structure or there might be another interface between the classical PCS domain and the monitoring and optimization domain is covered by the NAMUR open architecture concept (NOA) [10,11].…”
Section: Future Requirements To Communication/connectivitymentioning
confidence: 99%
“…Companies have also started to completely digitize their asset and plant plans. The question whether the high amount of information needs to be integrated in the classical pyramid automation structure or there might be another interface between the classical PCS domain and the monitoring and optimization domain is covered by the NAMUR open architecture concept (NOA) [10,11].…”
Section: Future Requirements To Communication/connectivitymentioning
confidence: 99%
“…One or more OPC UA aggregating servers integrate the plethora of distributed data sources into a coherent, central endpoint that makes the information available to the cloud. Third party applications can retrieve information from there and use it for data analytics, big data or device specific "as a service" optimizations without divulging the know-how required for the respective algorithm, offering the service result as an optimization suggestions [4].…”
Section: Noa Verification Of Requestmentioning
confidence: 99%
“…The acquisition of data from field devices or wireless sensors has been technologically feasible for a while. Many new industrial actuators and sensors are equipped with various (wireless) field bus technologies that permit accessing device specific information, such as runtime metrics or even integrated sensors [4] [5].Several initiatives have shown that this information can be accessed and forwarded to added value services. Most As the classic control structures of the automation pyramid are laid out for control and not flexible data acquisition, extracting this data through existent communication architectures would overburden the installed systems and -more critically -require the modification of installed, running and otherwise reliable assets.…”
Section: Namur Open Architecturementioning
confidence: 99%
“…Insbesondere am zuletzt genannten Punkt setzt die Namur Open Architecture (NOA) an. Sie stellt eine Erweiterung beziehungsweise eine Adaptionsmöglichkeit der klassischen Automatisierungspyramide für zusätzliche Funktionen bereit, siehe Bild 4 [12]. Zu NOA finden sich zwei weitere Aufsätze in dieser Ausgabe.…”
Section: Namur Open Architectureunclassified